Web directories: selected features and their impact on directory quality. Issue 3 (4th July 2016) - Jachimczyk, Adam; Chrapek, Magdalena; Chrapek, Zbigniew
Abstract : Purpose: – The purpose of this paper is statistical examination of nearly 7, 000 web directories and an analysis of factors which affect their quality measured by PageRank. Design/methodology/approach: – The authors analysed 6, 821 directories registered atwww.katalogiseo.info /. The following information about the directories was examined: the year of registration on the website, the directory's PageRank value, the existence of an active IP address, backlink requests, a fee charged for submission to the directory, as well as directory moderation and subject. Statistical analyses were performed with the use of Microsoft Excel, version 2010, and R software, version 3.0.0. The PageRank values were collected with a software written in Python. Findings: – The study has shown a gradual increase in popularity of directories as one of the basic tools in search engine optimisation. The analysis has indicated a relatively high percentage of spam web directories. The evidence of this is the number of directories with undetermined PageRank values. The study revealed that careful management of a directory and its subject have key impact on directory quality measured by PageRank. Originality/value: – Relatively few publications focus on the problem of web directories which represent a very large group of websites created solely to manipulate web search engine rankings. This paper discusses the phenomenon of web directories, reveals the percentage of spam directories, and factors which affect their quality measured by PageRank.